Examine the Impact of Using Digital Payment on Small and Medium Enterprises in Rwanda - Honorine, Umuhire (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
Abstract Rwanda's economic growth has come a long way in diverse sectors, including small and medium-sized firms (SMEs). The trend toward digitalization has made digital fee systems crucial for marketplace get entry to and financial efficiency. even as there were big-scale debates in the literature over the pros and cons of digital payments, there may be no clear adoption direction for Rwandan SMEs. This examination examines the readiness of SMEs to embrace digital payments using evaluating key enablers which including regulatory backing, technological infrastructure, and investment competencies. based totally on qualitative evidence, the research expounds on the impact of virtual payments on SME performance, monetary inclusion, and enterprise resilience. Findings imply that digital payments decorate transactional performance, lessen operating fees, and improve marketplace get right of entry to. notwithstanding these, massive-scale adoption is being stifled by way of vulnerable virtual infrastructure, inadequate virtual literacy, and security. Addressing the virtual divide, it's miles proposed that the private and non-private sectors converge through funding incentives, virtual literacy training, and bolstered cybersecurity. private universities can be partnered with SMEs as a good way to power innovation and know-how sharing, and government-supported schooling applications can drive the correct use of digital payments. Availability of strong internet connectivity and an excellent knowledge of digital finance may be critical for SMEs to contribute meaningfully to the virtual economy.